2004
DOI: 10.1089/088922204322749558
|View full text |Cite
|
Sign up to set email alerts
|

Protease Mutations in HIV-1 Non-B Strains Infecting Drug-Naive Villagers of Cameroon

Abstract: To describe the presence of protease inhibitor (PI) resistance-associated mutations and subtype distribution in drug-naive villagers of six provinces of Cameroon, we sequenced the protease (PR) gene (297 bp) of 128 viruses. Secondary PI resistance-associated mutations were identified at five sites: L10I/V (16%), K20R (8%), M36I (98%), L63P (13%), and V77I (6%). No primary mutation in the PR was identified. Of the 128 specimens analyzed, subtypes A (11%), C(2%), D (6%), F2 (3%), G (6%), H (0.8%), J (6%), and CR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 18 publications
4
18
1
Order By: Relevance
“…The prevalence of these mutations in this population differs from those described for subtype B viruses in the same codons. Thus while the frequency of mutations at codons 10, 20, and 36 was 2-7% among drug naïve individuals with subtype B infection, it was higher (21.74, 100 and 105%) in this study and in other studies (Hirsch et al, 2000;Konings et al, 2004;Fonjungo et al, 2002) of non-B viruses. These data provide baseline information on the level of drug resistance in this environment, where access to antiretroviral therapy is being scaled up.…”
Section: Discussioncontrasting
confidence: 62%
“…The prevalence of these mutations in this population differs from those described for subtype B viruses in the same codons. Thus while the frequency of mutations at codons 10, 20, and 36 was 2-7% among drug naïve individuals with subtype B infection, it was higher (21.74, 100 and 105%) in this study and in other studies (Hirsch et al, 2000;Konings et al, 2004;Fonjungo et al, 2002) of non-B viruses. These data provide baseline information on the level of drug resistance in this environment, where access to antiretroviral therapy is being scaled up.…”
Section: Discussioncontrasting
confidence: 62%
“…Unlike the case in developed countries, where antiretroviral regimens containing PIs are readily available, the first line of ART in Cameroon is the combination of two NRTIs plus one NNRTI. Very few patients in Cameroon are currently being or have been treated with PIs (1,(16)(17)(18). Konings et al (16) reported that only the minor mutations associated with PI resistance were detected among HIV-1-infected drug-naïve patients in Cameroon during the period of 2000 to 2002.…”
Section: Discussionmentioning
confidence: 99%
“…Very few patients in Cameroon are currently being or have been treated with PIs (1,(16)(17)(18). Konings et al (16) reported that only the minor mutations associated with PI resistance were detected among HIV-1-infected drug-naïve patients in Cameroon during the period of 2000 to 2002. Our study confirmed previous reports and describes a high frequency of minor mutations (isoleucine or valine at position 10 in CRF02_AG; K20I and M36I mutations), which were found in all sequences except one, i.e., the CMY-36 isolate classified as CRF11_cpx.…”
Section: Discussionmentioning
confidence: 99%
“…Upon arrival, plasma was aliquoted and stored at Ϫ70°C. Sequence and phylogenetic analysis was performed on a subset of the cohort demonstrating that the predominant clade type was the circulating recombinant form, CRF02_AG (3,5).…”
Section: Methodsmentioning
confidence: 99%